2019
DOI: 10.1186/s12863-019-0713-4
|View full text |Cite
|
Sign up to set email alerts
|

Sliding window haplotype approaches overcome single SNP analysis limitations in identifying genes for meat tenderness in Nelore cattle

Abstract: BackgroundTraditional single nucleotide polymorphism (SNP) genome-wide association analysis (GWAA) can be inefficient because single SNPs provide limited genetic information about genomic regions. On the other hand, using haplotypes in the statistical analysis may increase the extent of linkage disequilibrium (LD) between haplotypes and causal variants and may also potentially capture epistastic interactions between variants within a haplotyped locus, providing an increase in the power and robustness of the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 69 publications
0
34
0
Order By: Relevance
“…Future studies must benchmark the ability of the sequencing platforms assessed in this study for identifying and phasing other variants such as short insertion-deletion polymorphisms (indels) and structural variations such as larger insertion, deletions, duplications, and copy number variants (CNVs) which may play important roles in many diseases. Moreover, haplotype-based genome-wide association studies are gaining popularity for identifying trait associated genes [34]. Therefore, the ability to phase diploid genomes using long, highly accurate sequence data along with low-cost computation will push haplotype-based genome analysis to higher levels within livestock genomics.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies must benchmark the ability of the sequencing platforms assessed in this study for identifying and phasing other variants such as short insertion-deletion polymorphisms (indels) and structural variations such as larger insertion, deletions, duplications, and copy number variants (CNVs) which may play important roles in many diseases. Moreover, haplotype-based genome-wide association studies are gaining popularity for identifying trait associated genes [34]. Therefore, the ability to phase diploid genomes using long, highly accurate sequence data along with low-cost computation will push haplotype-based genome analysis to higher levels within livestock genomics.…”
Section: Discussionmentioning
confidence: 99%
“…Fragomeni, et al [42] also reported that small window sizes are accompanied with large noises. Furthermore, it has been shown that single-SNP GWAS cannot be effective enough, because single-SNPs provide limited information about the content of flanking genomic regions [43][44][45]. In the present study, 50-adjacent SNP windows (with an average of 165 Kb widow size) that explained equal to or more than 0.20% of the genetic variance was considered as the threshold for significance.…”
Section: Variance Components and Accuracy Of Genomic Predictionsmentioning
confidence: 95%
“…We also performed single‐marker SNP tests to offer a comparison of their sensitivity to that of haplotype‐based markers in the same population. Differences in power and sensitivity of single SNPs compared to haplotypes and how these are calculated have been shown by other studies using simulated and empirical data in pigs and cattle, in humans and in barley (Braz et al, ; Clark, ; Gabriel et al, ; Hamon et al, ; Karimi et al, ; Lorenz et al, ; Meuwissen et al, ; Morris Rw, ; Wu et al, ). In the present study, we therefore concentrated on applying those principles with the aim of exploiting the advantages of single‐SNP and haplotype methods to enhance the detection of polymorphisms with potential roles in spinach–anthracnose interactions.…”
Section: Discussionmentioning
confidence: 87%
“…A number of studies have rationalized grouping SNPs into haplotype blocks because of the ability to improve power, robustness and accuracy of association mapping in humans (Gabriel et al, ), animals (pigs and cattle) (Karimi, Sargolzaei, JaB, & Schenkel, ; Meuwissen, Odegard, Andersen‐Ranberg, & Grindflek, ) and plants (barley) (Lorenz, Hamblin, & Jannink, ). Using haplotypes may also capture more LD between haplotypes and causal variants (Braz et al, ; Wu et al, ); provide more power than single SNPs when an allelic series exists at a locus (Morris Rw, ); potentially capture epistatic interactions between variants within a haplotyped locus (Clark, ; Hamon et al, ); and even allow informed testing between two alleles showing IBD and clades of haplotype alleles by capturing information from evolutionary history (Calus et al, ; Zhao, ).…”
Section: Introductionmentioning
confidence: 99%